2020
DOI: 10.3390/electronics9010163
|View full text |Cite
|
Sign up to set email alerts
|

Design of Reconfigurable Bandwidth Filtering Antenna and Its Applications in IR/UWB System

Abstract: A reconfigurable bandwidth antenna for an impulse radio-UWB (IR/UWB) system design is illustrated in this paper. By adopting a continuously tunable low-pass filter by varactor at the feed of the antenna, the proposed antenna obtains a continuous tunable bandwidth from 1.02 GHz to 2.42 GHz. To ensure the identifiability of transmitted pulses in (IR-UWB) system, the antenna is analyzed in both frequency domain and time domain. The proposed antenna is valid with a system fidelity factor (SFF) above 0.8 while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Unlike the research in ref. [13][14][15][16][17][18][19][20], the present research is tested for MIMO technology and promising results are obtained. 7.…”
Section: Megmentioning
confidence: 88%
See 4 more Smart Citations
“…Unlike the research in ref. [13][14][15][16][17][18][19][20], the present research is tested for MIMO technology and promising results are obtained. 7.…”
Section: Megmentioning
confidence: 88%
“…Unlike the research reported in ref. [13][14][15][16][17][18][19][20][21], the proposed bandwidth switchable antenna works for the entire UWB band and the narrow band with high fractional bandwidth. 3.…”
Section: Megmentioning
confidence: 99%
See 3 more Smart Citations